Innovation and technology in multimodal supply chains - Lóránt A. Tavasszy (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper investigates innovations in multimodal supply chains. It covers innovations in technology and IT, physical hardware and how supply chains are organised. It outlines direct and indirect impacts of these innovations, showing the ramifications for multimodality, the broader logistics system and sustainability challenges.
Keywords: 330